Pemanfaatan Sistem Photovoltaic untuk Catu Daya Repeater Radio PLN - Suhardhika Sih Sudewanto; Erwin Kalatiku (Sekolah Tinggi Teknik PLN, 2021)
The utilization of radio communication is one of several means to carry out electricity network coordination. The establishment of radio repeater is mandatory to cover vast areas of electricity system nodes. The radiation of a radio system is generally restricted by the contour of the terrain. The optimal location for radio repeater is usually situated in an isolated area, away from society. This will cause a problem in acquiring power supply from the local grid. This problem can be solved by harnessing solar power to energize the photovoltaic system. The implementation of the photovoltaic system will be done by performing load calculations of radio repeater equipment, determining the components needed, and executing site installation. With calculation result of 6,3 Days of Autonomy, the photovoltaic system is believed to be robust enough to increase the effectiveness of radio repeater operation.